Contribution of Grip Strength, Arm Muscles and Back Muscles to Long Stroke Accuracy in Woodball (Journal of Physical Education and Sports, 2021)
This study aims to analyze and examine how the contribution of grip strength, arm muscle strength and back muscle strength to the accuracy of long stroke on woodball. This study uses a correlational design with the variables of grip strength, arm muscle strength and back muscle strength to long stroke accuracy. The samples in this study were 25 Central Java woodball athletes using handgrip dynamometer, pull and push dynamometer, back dynamometer and long shot test. The result of this research is that the grip strength contributes 3.1%. Arm muscle strength contributed 13.9%. Back muscle strength contributed 1.5%. Grip strength and arm muscle strength together contributed 13.9%. Grip strength and back muscle strength contributed 48%. Arm muscle strength and back muscle strength together contributed 14%. Grip strength, arm muscle strength and back muscle strength together contributed to long stroke accuracy by 14%.